Biogeography of pelagic food webs in the North Pacific. (12th March 2018) - Piatt, John F.; Arimitsu, Mayumi L.; Sydeman, William J.; Thompson, Sarah Ann; Renner, Heather; Zador, Stephani; Douglas, David; Hatch, Scott; Kettle, Arthur; Williams, Jeff
Abstract: The tufted puffin ( Fratercula cirrhata ) is a generalist seabird that breeds throughout the North Pacific and eats more than 75 different prey species. Using puffins as samplers, we characterized the geographic variability in pelagic food webs across the subarctic North Pacific from the composition of ~10, 000 tufted puffin meals (~56, 000 prey items) collected at 35 colonies in the Gulf of Alaska (GoA) and Aleutian Archipelago. Cluster analysis of diet species composition suggested three distinct forage fish communities: (i) in the northern GoA, multiple age‐classes of coastal and shelf residents such as capelin, sand lance and herring dominated the food web, (ii) in the western GoA to eastern Aleutians, the shelf community was dominated by transient age‐0 walleye pollock, and (iii) in the western Aleutians, shelf‐edge and mesopelagic forage species such as squid, lanternfish, and Atka mackerel were prevalent. Geographic patterns of abundance of capelin and sand lance in tufted puffin diets were corroborated by independent research fisheries and diets of piscivorous fish, indicating that puffin diets reflect the local abundance of forage species, not just selection of favored species. Generalized additive models showed that habitat characteristics predict, in a non‐linear fashion, forage species distribution and abundance across two large marine ecosystems. We conclude that major biogeographic patterns in forage fish distribution follow gradients in key habitat features, and puffin diets reflect those patterns.